1997
DOI: 10.1128/iai.65.3.931-935.1997
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Cryptococcus neoformans to heterologously expressed human complement receptors

Abstract: Previously, we demonstrated that monoclonal antibodies (MAb) directed against any of the three defined complement receptors (CR) for the third component of complement (CR1, CR3, and CR4) profoundly inhibited the binding of serum-opsonized Cryptococcus neoformans to monocyte-derived macrophages. These studies suggested either that a synergistic interaction between multiple CR was required for optimal binding of C. neoformans or that the MAb were exerting nonspecific effects (such as receptor coassociation). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…Although prior investigators have shown that serum‐mediated binding of C. neoformans by human phagocytes is mediated through CR 32, this process had not been investigated with murine cells. We used mAb against CR subunits to investigate the involvement of these receptors in the phagocytosis of C. neoformans strains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prior investigators have shown that serum‐mediated binding of C. neoformans by human phagocytes is mediated through CR 32, this process had not been investigated with murine cells. We used mAb against CR subunits to investigate the involvement of these receptors in the phagocytosis of C. neoformans strains.…”
Section: Resultsmentioning
confidence: 99%
“…CR1 was dispensable, and CR4 played a role only in some strains. This suggests a species difference between mouse and human cells, since the latter have been shown to ingest complement‐opsonized C. neoformans through CR1, CR3, and CR4 32, 34. This discrepancy could indicate that the affinity of the CR for the different forms of C3 varies between the species and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…116 The complement receptors CR1, CR3 and CR4 are the main effector molecules to mediate binding and phagocytosis of cryptococci, as demonstrated by monoclonal antibodies against the three receptors that block binding of the yeast cells. 117,118 A ranking for the CRs demonstrates the dominance of CR3. 112 The complement receptors CR3 and CR4 are also involved in complement-independent, antibody-mediated phagocytosis of C. neoformans.…”
Section: Complement-mediated Effector Mechanisms In Cryptococcal Infementioning
confidence: 99%
“…Further studies established that CR1, CR3 and CR4 act independently of each other in their binding opsonized Cr. neoformans 70 . The complement receptors CR3 and CR4 are also involved in the complement‐dependent antibody‐mediated phagocytosis of C. neoformans .…”
Section: Complement and Cryptococcosismentioning
confidence: 99%